Correlation between interferon γ and interleukin 6 with PTSD and resilience. (February 2018) - Bruenig, Dagmar; Mehta, Divya; Morris, Charles P.; Lawford, Bruce; Harvey, Wendy; McD Young, Ross; Voisey, Joanne
Abstract: Posttraumatic Stress Disorder (PTSD) is a debilitating psychiatric disorder with decreased general health prognosis and increased mortality. Inflammation has been hypothesised to be a link between PTSD and the most common co-morbid medical disorders. However, the relationship between inflammation and PTSD is not clear. Individual inflammatory markers have shown variable associations with PTSD. This study investigates the correlations between serum cytokines, PTSD and resilience in a cohort of Caucasian Vietnam combat veterans ( n = 299). After correction for multiple testing, PTSD severity was correlated with small but significant decreases in interleukin 6 and interferon γ ( p = 0.004, p = 0.013, respectively) whereas resilience was correlated with increased levels of interleukin 6 and interferon γ ( p = 0.023; p = 0.007, respectively). Analyses of sub-symptoms of PTSD revealed that mood and arousal symptoms showed the most significant effect on interleukin 6 and interferon γ. More research is needed to further elucidate the mechanisms underlying the relationship between cytokine levels, PTSD sub-symptoms and trauma outcomes to improve the knowledge base of differences in trauma response and the biological system. Highlights: Large cohort of tightly trauma-screened veterans to test the relationship tests between serum IFNγ and PTSD and resilience. Significant correlation of Interferon γ (IFNγ) and interleukin α (IL α) with PTSD severity. Relationship of IFNγ, IL α and PTSD severity likely driven by specific sub-symptoms. Significant correlation of IFNγ. IL αand resilience.